Structural changes and cellulose ultrastructure mapped with electron microscopy and SAXS after enzymatic hydrolysis of mildly steam pretreated Norway spruce - Maria E. F. Brollo; Fabio Caputo; Polina Naidjonoka; Lisbeth Olsson; Eva Olsson (Biotechnology for Biofuels and Bioproducts)
Abstract Background The efficient use of softwood in biorefineries requires harsh pretreatment conditions to overcome biomass recalcitrance. While this allows the solubilization of hemicellulose, it also leads to the formation of compounds that act inhibitory against microorganisms during the fermentation step. To improve the efficacy of biomass utilization and identify optimal processing conditions, we evaluated the microstructural alterations occurring during pretreatment and enzymatic hydrolysis in Norway spruce. The biomass was steam pretreated at six different severities defined by two different temperatures (180 °C and 210 °C), with and without the addition of various acids (HAc, H3PO4, H2SO4, SO2). After pretreatment, the materials were enzymatically hydrolysed using a cellulolytic cocktail (Celluclast + Novozym188) supplemented with a hemicellulolytic cocktail (Ultraflo). Scanning electron microscopy and small angle X-ray scattering were utilized to evaluate the structural changes, of the differently steam pretreated materials, before and after the enzymatic hydrolysis. Results Scanning electron microscopy revealed increased surface roughness and pore enlargement in all the materials after enzymatic hydrolysis. The higher the severity of the pretreatment, the more the surface was rough since it was easier for the enzymes to access the binding site. As revealed by small angle X-ray scattering (SAXS), increasing the enzymatic hydrolysis of hemicellulose did not result in further collapse of cellulose. In line with the SAXS result, a qualitative evaluation of the cellulose surface using Congo red showed a larger exposed cellulose surface area after enzymatic hydrolysis. Conclusions The present study reports the microstructural changes caused by pretreatment and enzymatic hydrolysis of Norway spruce. By enzymatically increasing the hemicellulose hydrolysis, the exposed cellulose surface area increases meaning that the cellulose might be easier to access for the enzymes. Structural analysis of biomass after enzymatic hydrolysis can direct the choice of enzymes for improved saccharification efficiency.